1998
DOI: 10.1259/bjr.71.843.9616234
|View full text |Cite
|
Sign up to set email alerts
|

Virtual cystoscopy based on helical CT scan datasets: perspectives and limitations.

Abstract: The purpose of the study was to simulate cystoscopy based on three-dimensional helical CT scan datasets in real-time in patients with tumours of the urinary bladder. A helical CT scan with double detector technology was carried out pre-operatively in 11 patients with histologically confirmed carcinoma of the urinary bladder and one patient with chronic cystitis. A non-enhanced scan was first performed, followed by an examination in the early phase of contrast medium enhancement. Further images were acquired af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 11 publications
2
23
0
5
Order By: Relevance
“…This technique, first used by Merkle et al, 18 is a minimally invasive method. It can be carried out as a component of routine abdominopelvic CT investigation with contrast.…”
Section: Discussionmentioning
confidence: 99%
“…This technique, first used by Merkle et al, 18 is a minimally invasive method. It can be carried out as a component of routine abdominopelvic CT investigation with contrast.…”
Section: Discussionmentioning
confidence: 99%
“…In phase III trial, there was one case of bladder cancer that was detected by HAL fluorescence cystoscopy that was missed by white light cystoscopy (Grossman et al, 2007). Study on efficacy of virtual cystoscopy in patients with bladder tumors shows that its use is still in its infancy and has not yet reached the acceptable quality of fibreoptic examination (Merkle et al, 1998). Yet another study found that in comparison with standard cystoscopy, narrow-band imaging could better detect "nonmuscle-invasive bladder tumors" (Herr and Donat, 2008).…”
Section: Diagnostic Usesmentioning
confidence: 99%
“…Ebenso ist es möglich, jodhaltiges Kontrastmittel i.v. zu verabreichen, und die Füllung der Blase mit kontrastiertem Urin abzuwarten [16]. Dies hat den Vorteil, keinen Blasenkatheter legen zu müssen, birgt aber das geringe Risiko einer Unverträglichkeitsreaktion auf jodhaltiges Kontrastmittel.…”
Section: Rohdatenerfassung Mittels Ctunclassified